2022
DOI: 10.1680/jenge.18.00158
|View full text |Cite
|
Sign up to set email alerts
|

Effect of stress history of saturated clay on engineering behaviour of an energy pile

Abstract: The mechanical properties of soil could be affected by its temperature change and these effects may lead to additional issues in the thermo-mechanical behaviour of energy piles. Laboratory experiments were conducted to assess the thermo-mechanical behaviour of a small-scale instrumented energy pile installed in a saturated clay at different stress histories. The energy pile was subjected to five heating/cooling cycles. The experimental programme involved monitoring the changes in the surrounding soil temperatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 40 publications
0
1
0
Order By: Relevance
“…The gradual accumulation of thermally-induced irreversible horizontal displacements during thermal cycles could be caused by thermally-induced passive soil resistance mobilization. This kind of ratcheting response was similarly observed for axially-loaded energy piles embedded in clay reported by Nguyen et al (2020), Wu et al (2020) and Ng et al (2014Ng et al ( , 2021a, and for horizontally-loaded energy pile embedded in dry sand reported by Zhao et al (2022). 13…”
Section: Resultssupporting
confidence: 74%
See 2 more Smart Citations
“…The gradual accumulation of thermally-induced irreversible horizontal displacements during thermal cycles could be caused by thermally-induced passive soil resistance mobilization. This kind of ratcheting response was similarly observed for axially-loaded energy piles embedded in clay reported by Nguyen et al (2020), Wu et al (2020) and Ng et al (2014Ng et al ( , 2021a, and for horizontally-loaded energy pile embedded in dry sand reported by Zhao et al (2022). 13…”
Section: Resultssupporting
confidence: 74%
“…Additionally, thermally-induced soil consolidation and creep could contribute in turn to a time-dependent increase in horizontal displacement during the recovery phase. Evidence of these phenomena are available in previous works (Akrouch et al 2014;Wu et al 2020;Ng et al 2014Ng et al , 2021a. The gradual accumulation of thermally-induced irreversible horizontal displacements during thermal cycles could be caused by thermally-induced passive soil resistance mobilization.…”
Section: Resultsmentioning
confidence: 70%
See 1 more Smart Citation
“…Scholars at home and abroad have carried out much research in the related areas of this study [19,20,[24][25][26][27][28]. Wu et al [29] started with the stress history of soil and found that compared with overconsolidated clay, normally consolidated clay exhibits higher irreversible pile head settlement and pile end resistance. Through laboratory experiments, Liu et al [30] found that the moisture content of the sand around the energy pile affects the frictional resistance at the pile-soil interface caused by temperature.…”
Section: Introductionmentioning
confidence: 99%